The identification of a new alternative exon with highly restricted tissue expression in transcripts encoding the mouse Pgp-1 (CD44) homing receptor. Comparison of all 10 variable exons between mouse, human, and rat. - Screaton, G; Bell, M; Bell, J; Jackson, D (1993)
The human CD44 cell surface glycoprotein family which has been implicated in lymphocyte homing, tumor metastasis, and extracellular matrix attachment consists of a large number of related isoforms that derive from the differential splicing of a single CD44 gene transcript. Recent mapping of the CD44 locus in man indicated the presence of at least nine alternative exons within the region of the gene encoding the variable membrane proximal extracellular domain. Here we report the identification of a 10th alternative exon (termed V1) in the mouse, human, and rat CD44 genes. We demonstrate tissue-specific patterns of expression for transcripts containing exons V1-V10 in the mouse and a highly restricted usage of exon V1 in transcripts from mouse gastric tissue. Close sequence homology between exons V1-V10 from mouse rat and human points to a specific functional role rather than a purely structural role for the membrane proximal extracellular domain of the CD44 molecule.